Creators’ Creation of the Universe: An Ecological Implication in Chait Mundhum - Kandangwa, Bed Prakash (Dristikon: A Multidisciplinary Journal, 2024)
This article deals with the creators’ creation of the universe as an ecologically interconnected world in Bairagi Kainla’s Chait Mundhum. The whole ecosphere and its components—biotic and abiotic—are not good and beautiful until the earth and human being is created by Tagera Ningwaphu Mang and her successor, Porokmi Mang. In initial phase, Tagera Ningwaphu Mang perceives her creation not suitable. She creates five major abiotic substances: sky, sun, air, earth, and water to address this problem. The middle phase extends with the beautification of earth by Porokmi Mang creating several organisms and species such as forests, flowers, insects, animals and mammals. The creators also manage water to each biotic and abiotic factor. To sustain the created world, each organisms and species are afforded with food and shelter. The creators become satisfied only in their final creation of man. They evaluate their creation beautiful and perfect in complementary existence of other things. Everything is interconnected in the creation. Therefore, Chait Mundhum mentions these ecological features implicated in the creation of the universe. To back up this, Barry Commoner’s principle of ecology has been used as a theoretical model. Subsequent Mundhums associated with this theme has also been used to support the claim. The article will be useful to those researchers and critics who want to study other Mundhums from the ecological perspective.